KAJIAN DEBIT BANJIR PADA DRAINASE JALAN APT PRANOTO KECAMATAN SANGATTA UTARA - SULKIFLI, ANDY (KURVA S JURNAL MAHASISWA, 2014)
Subdistrict North Sangatta, especially on the road Pranoto Apt is an area that is oftenflooded it is known by flood inundation maps and tables of points floodwaters City North Sangattaobtained from the Department of Public Works District. East Kutai. This thesis aims to analyze theability of existing drainage channels (existing) to accommodate surface runoff and stream flow,condition, shape, construction and see the direction of the flow channel in the area of thefloodwaters. Boundary problem in terms of this thesis is a hydrological analysis to analyze rainfallplans, rainfall intensity and time of concentration, while the analysis of hydraulics for analyzingthe ability of the secondary channels that already exist (existing) in a location that is reviewed isthe path Apt Pranoto District of North Sangatta to accommodate runoff and streamThe method used is the method of data collection and analysis. The data used are primarydata and secondary data are then analyzed based on the analysis of hydrology and hydraulicsanalysis and evaluated based on the value of the existing discharge chute with discharge planvalue.To determine rainfall plans to use two types of distributions are widely used in the fieldsof hydrology, distribution Person Log III and Gumbel distribution, then take the value of rainfallover a period of 2, 5, 10, 25 years of Distribution Log Person III to be used in further calculations.The time is determined by the equation concentration tc = to + td, rainfall intensity withMononobe method, discharge plan is calculated based on the Rational method and the evaluationof the channel cross section â‰¥ Qs equation QT.Rainfall value used to calculate the intensity of rainfall is the rainfall distribution value LogsPerson III repeated periods of 2.5, 10, 25 years,. From the analysis of the dimensions of thechannel turns all channels capable of accommodating the discharge channel to the next 25.